I think of a number multiply it by 3 and add 6 the result is 21 what is the number

Answers

Answer 1
Answer:

Answer:

5

Step-by-step explanation:

5x3=15

15+6=21

Hope this helped pls give brainliest


Related Questions

What is the half of 62
The order pair (0 , 0) is a solution to the inequality y < x -2 FalseorTrue
Which process consists of a logical chain of steps
Molly owes her brother $300.She works for $10 per hour as a checker at the local grocery store.Molly plans to repay her brother half of what she earns after taxes of 20% are taken out.Identify the expression which represents the condition described
Which type of quadrilateral has two pairs of parallel sides and four congruent sides?A. trapezium B. kite C. trapezoid D. rhombus

I need answer ASAP I’m next 10 mins

Answers

Answer:

B

Step-by-step explanation:

First simplify the first term to get

10y^4

then multiply 10y^4 by 4 square root 6y^3

40y would be all you needed to get answer

Answer:

40y^5√6y (B)

Step-by-step explanation:

Let's multiply 2√25y^8 * 4√6y^3:

8√150y^11 (When you multiply exponents with the same base, you can just add the exponents and keep the same base:

Ex. 4^5 * 4^9 = 4^14)

Let's simplify 8√150y^11

√150 = 5√6

√y^11 = y^5√y

So our final answer would be:

40y^5√6y

The weight of an object on the moon varies directly with its weight on Mars. If an object weighing 110 g on the moon weighs 250 g on mars, how much does an object weigh on the moon if it weighs 100 g on Mars?

Answers

Answer: 44g is the answer

Solve for v -3v+11=-8v+51 Simplify your answer as much as possible.

Answers

Answer:

v = 8

Step-by-step explanation:

  • Solve for v -3v+11=-8v+51 Simplify your answer as much as possible.

-3v + 11 = -8v + 51

-3v + 8v = 51 - 11

5v = 40

v = 40 : 5

v = 8

--------------------------

  • check

-3(8) + 11 = -8(8) + 51

-24 + 11 = -64 + 51

-13 = -13

What is 34/51 in its simplest form

Answers

2/3
divide by 17

34/17 is 2
51/17 is 3

The difference between an observational study and an experiment is thatA . in an observational study, only one group is studied, and in an experiment, two groups are studied.

B . in an observational study, the researchers do not control treatment, and in an experiment, they do.

C . in an experiment, cause-and-effect is analyzed, and in an observational study, it is not.

D . in an experiment, one group is studied over a short period of time, and in an observational study, the group is studied over a longer period of time.

Answers

Answer: (b) in an observational study, the researchers do not control treatment, and in experiment, they do.

Step-by-step explanation: In an observational study, only one group is studied, but in an experiment, more than one, may be two, three, etc. are studied, so option (A) is not correct. In an observational study, researchers control treatment but in experiment they do not, and so, option (B) is also incorrect. Option (D) is not correct, because a group is studied over a longer period of time in an experiment and the group is studied over a short period of time in observational study. The only correct option is (C) because cause and effect is studied in an experiment and are not studied in an observational study.

Hence, (C) is the correct option.



Answer:

b

Step-by-step explanation:

edge 21

IF YOU GET THIS ALL RIGHT ILL GIVE AWAY 99 POINTS!!!!!Problem 1: Solve the equation

5(-3x - 2) - (x - 3) = -4(4x + 5) + 13

Problem 2: Simplify the expression

2(a -3) + 4b - 2(a -b -3) + 5

Problem 3: If x <2, simplify

|x - 2| - 4|-6|

Problem 4: Find the distance between the points (-4 , -5) and (-1 , -1).

Problem 5: Find the x intercept of the graph of the equation .

2x - 4y = 9

Problem 6: Evaluate f(2) - f(1)

f(x) = 6x + 1

Problem 7: Find the slope of the line passing through the points (-1, -1) and (2 , 2).

Problem 8: Find the slope of the line

5x - 5y = 7

Problem 9: Find the equation of the line that passes through the points (-1 , -1) and (-1 , 2).

Problem 10: Solve the equation

|-2x + 2| -3 = -3

Answers

Simplifying -2x + -4y = 9 Solving -2x + -4y = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. -2x + -4y + 4y = 9 + 4y Combine like terms: -4y + 4y = 0 -2x + 0 = 9 + 4y -2x = 9 + 4y Divide each side by '-2'. x = -4.5 + -2y Simplifying x = -4.5 + -2y13/18

169
-11

5x - 5y = 7


Simplifying -2x + -4y = 9 Solving -2x + -4y = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. -2x + -4y + 4y = 9 + 4y Combine like terms: -4y + 4y = 0 -2x + 0 = 9 + 4y -2x = 9 + 4y Divide each side by '-2'. x = -4.5 + -2y Simplifying x = -4.5 + -2y13/18


169

-11


5x - 5y = 7



Read more on Brainly.com - brainly.com/question/1639237#readmore